2015
DOI: 10.1073/pnas.1508436113
|View full text |Cite
|
Sign up to set email alerts
|

Functional hierarchy underlies preferential connectivity disturbances in schizophrenia

Abstract: Schizophrenia may involve an elevated excitation/inhibition (E/I) ratio in cortical microcircuits. It remains unknown how this regulatory disturbance maps onto neuroimaging findings. To address this issue, we implemented E/I perturbations within a neural model of large-scale functional connectivity, which predicted hyperconnectivity following E/I elevation. To test predictions, we examined restingstate functional MRI in 161 schizophrenia patients and 164 healthy subjects. As predicted, patients exhibited eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
141
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 105 publications
16
141
1
Order By: Relevance
“…The temporal coordination of node allegiances to neural systems is at the core of the quantified network flexibility measure, and our node-wise supplemental analyses highlighted a systemwide (rather than a regionally confined) increase in network flexibility in the patients and relatives. However, these findings do not argue against a differential or preferential involvement of certain brain areas at different hierarchical levels (34). For the proposed excitatory-inhibitory imbalance of neural networks in schizophrenia, altered NMDA receptor-depending input to fast-spiking γ-aminobutyric acid (GABA) interneurons has been repeatedly highlighted as a key molecular candidate mechanism for schizophrenia (5,25,35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal coordination of node allegiances to neural systems is at the core of the quantified network flexibility measure, and our node-wise supplemental analyses highlighted a systemwide (rather than a regionally confined) increase in network flexibility in the patients and relatives. However, these findings do not argue against a differential or preferential involvement of certain brain areas at different hierarchical levels (34). For the proposed excitatory-inhibitory imbalance of neural networks in schizophrenia, altered NMDA receptor-depending input to fast-spiking γ-aminobutyric acid (GABA) interneurons has been repeatedly highlighted as a key molecular candidate mechanism for schizophrenia (5,25,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Here, further research is warranted, including pharmacological experiments in schizophrenia patients and their healthy first-degree relatives. Fourth, although the idea of an excitatoryinhibitory imbalance is a popular concept in current psychiatric neuroscience (34,46), the biological mechanisms require further clarification. Specifically, although the ubiquitous presence of glutamatergic neurons and NMDA receptors across the brain makes distributed genetic risk effects at the neural network level plausible, further translational research is needed to dissolve some of the ambiguities of this pathophysiological concept.…”
Section: Discussionmentioning
confidence: 99%
“…As a step in this direction, such an extension has been explored in heterogeneity of local recurrent connectivity across cortical hierarchy. Yang et al (2016) found that elevated E/I ratio in a homogenous model yielded elevated mean functional connectivity, as measured by covariance of the BOLD signal. In line with this model prediction, analysis of resting-state fMRI revealed that this connectivity is increased in SCZ, but that this increase is preferential in association cortex relative to sensory cortex (Fig.…”
Section: Computational Models Of Thalamocortical Dynamicsmentioning
confidence: 92%
“…Thus far these models have primarily applied to cortex only, without inclusion of thalamus or other subcortical structures. In a series of studies, we applied these models to study the large-scale impact of alterations in the excitation-inhibition (E/I) ratio in cortical circuits, relating these effects to rs-fcMRI biomarkers in SCZ (Yang et al, 2014; Anticevic et al, 2015b; Yang et al, 2016). Yang et al (2014) found that increasing the effective strength of connectivity at either the local or long-range level, resulting in an elevated E/I ratio, can capture the elevated local and global neural variability observed in SCZ.…”
Section: Computational Models Of Thalamocortical Dynamicsmentioning
confidence: 99%
“…For example, schizophrenia patients show altered electroencephalograph (EEG) event related potentials (ERPs) in response to auditory and visual stimuli, as well as altered neural activation in sensory cortices during fMRI studies of sensory processing [105,119,120]. Schizophrenia patients also show altered activation across many individual brain regions and altered connectivity within large-scale brain networks during a variety of sensory and cognitive tasks, although, relative to sensory regions, activation and connectivity involving association cortices may be more disrupted [121-123]. Similarly, schizophrenia patients show altered neural oscillations, as measured by EEG and magnetoencephalography (MEG), during sensory and cognitive tasks, as well as at rest [123,124], with gamma-band oscillations thought to show particular disturbance.…”
Section: Figurementioning
confidence: 99%